Bibliometric and Visual Analysis of Vascular Calcification Research - Dong, Qian; Liang, Qingchun; Chen, Ying; Li, Jinhe; Lu, Lihe; Huang, Xiongqing; Zhou, Qin (Frontiers in Pharmacology, 2021)
Background: Extensive studies related to vascular calcification (VC) were conducted in recent years. However, no bibliometric analysis has systematically investigated this topic. Our study aimed to determine the hotspots and frontiers of VC research in the past decade and provide a reference for future scientific research directions and decision-making in the VC field. Methods: VC studies were acquired from the Web of Science Core Collection. Bibliometric and visual analyses were performed using CiteSpace, VOSviewer, and Microsoft Excel software. Results: A total of 8,238 English articles on VC research published in 2011–2020 were obtained. In the past decade, annual publications and citations showed a significant growth trend, especially in 2018–2020. The most productive country, institution, journal and author are the United States, the University of California System, PLOS ONE, and Budoff MJ, respectively. The most frequently cited country, journal, and author are the United States, Journal of the American College of Cardiology, and Floege J, respectively. “Vascular calcification,” “atherosclerosis,” “chronic kidney disease,” and “cardiovascular disease” are the primary keywords. The burst keywords “revascularization,” “calciprotein particle,” “microRNA,” and “microcalcification” are speculated to be the research frontiers. Conclusion: The main research hotspots in the VC field are the molecular mechanisms and prognosis of VC in patients with chronic kidney disease or cardiovascular disease. In addition, endovascular therapy and the development of new drugs targeting signal pathways for VC will become the focus of future research. Moreover, non-coding RNAs related to the diagnosis and treatment of VC are great research prospects.